Landscape preference among Chinese visitors to Chinese elements in a Japanese Garden. (August 2018) - Meng, D; Matsumoto, T; Mizuuchi, Y; Furuya, K
Abstract: Koishikawa Korakuen is an Edo-period garden in Japan that was inspired by scenes typical of Chinese gardens. This study aimed to clarify how Chinese tourists evaluate the Chinese elements at Koishikawa Korakuen and compare landscape preferences. The preferred landscapes were determined and analyzed using visitor-employed photography, GPS, and questionnaires. Fifty-seven Chinese visitors were asked to take photos in the garden and select their 10 favourites from among them. GIS was used to identify the positions of the preferred photos. The results indicate that "Full-Moon Bridge" is the most Chinese-looking landscape at Koishikawa Korakuen; the second is the lotus pond. Moreover, spatial analysis was conducted by dividing the garden into six areas. Within these six areas, seven locations showed high levels of appreciation. This study's findings help to clarify the elements Chinese visitors prefer at Koishikawa Korakuen as well as the differences among Chinese and Japanese visitors regarding landscape preferences in Chinese-style gardens.